Uncaria gambir Roxb Leaf Extract Mediated Hydrothermal Synthesis of Magnetite Nanoparticles - Amrulloh, Yasir; Syukri, Syukri; Emriadi, Emriadi; Hardi, Anla Fet; Arief, Syukri (Proceeding International Conference on Religion, Science and Education, 2025)
This study aims to investigate the effect of UGR plant extract in the synthesis process of magnetite nanoparticles (MNPs). Uncaria gambir Roxb (UGR) leaves contain bioactive compounds that can interact with magnetite precursors. Magnetite nanoparticles were synthesized through hydrothermal method between FeCl3 and UGR extract. The results showed that the use of UGR extract in the synthesis of magnetite nanoparticles produced a significant effect on the crystal structure. There is a change in the crystal lattice parameters of the nanoparticles synthesized with UGR extract compared to the nanoparticles synthesized without the use of the extract. In addition, the particle size of magnetite nanoparticles also decreased significantly, with a more homogeneous particle size distribution in magnetite nanoparticles involving UGR extract. Furthermore, this study also proved that UGR extract has an influence on the magnetic properties of the nanoparticles produced. MNPs with UGR extract showed stronger magnetic properties compared to nanoparticles synthesized without UGR extract. This indicates that UGR extract can act as a reducing agent in the synthesis process of magnetite nanoparticles. This research provides new insights into the use of UGR plant extract in the synthesis of magnetite nanoparticles and broadens our understanding of the interaction between natural compounds and magnetic materials. It is hoped that the results of this study can serve as a foundation for the development of new applications of magnetite nanoparticles synthesized using UGR extract.